Analysis of hydrogen fueling, recycling, and confinement at Wendelstein 7-X via a single-reservoir particle balance. (1st March 2022) - Kremeyer, Thierry; König, R.; Brezinsek, S.; Schmitz, O.; Feng, Y.; Winters, V.; Rudischhauser, L.; Buttenschön, B.; Brunner, K.J.; Drewelow, P.; Flom, E.; Fuchert, G.; et al.
Abstract: A single-reservoir particle balance for the main plasma species hydrogen has been established for W7-X. This has enabled the quantitative characterization of the particle sources in the standard island divertor configuration for the first time. Findings from attached scenarios with two different island sizes with a boronized wall and turbo molecular pumping are presented. Fueling efficiencies, particle flows and source locations were measured and used to infer the total particle confinement time τ p . Perturbative gas injection experiments served to measure the effective particle confinement time τ p * . Combining both confinement times provides access to the global recycling coefficient R ¯ . Hydrogen particle inventories have been addressed and the knowledge of particle sources and sinks reveals the core fueling distribution and provides insight into the capability of the magnetic islands to control exhaust features. Measurements of hydrogen fueling efficiencies were sensitive to the precise fueling location and measured between 12% and 31% with the recycling fueling at the strike line modeled at only 6%, due to much higher densities. 15% of the total 5.2 × 10 22 a/s recycling flow ionizes far away from the recycling surfaces in the main chamber. It was shown that 60% of recycled particles ionize above the horizontal and 18% above the vertical divertor target, while the remainder of the recycling flow ionizes above the baffle (7%). Combining these source terms with their individual fueling efficiencies resolves the core fueling distribution. Due to the higher fueling efficiency in the main chamber, up to 51% of the total 5.1 × 10 21 s −1 core fueling particles are entering the confined plasma from the main chamber. τ p values in the range of 260 ms were extracted for these discharges. Together with τ p, the global recycling coefficient R ¯ was resolved for every τ p * measurement and a typical value close to unity was obtained. An increase of the island size, resulted in no change of τ p, but doubled τ p *, indicating the feasibility of the control coils as an actuator to control exhaust features without affecting core confinement properties.